Systemic and Local Phenotypes of Barium Chloride Induced Skeletal Muscle Injury in Mice - Hee-Won Jung (Annals of Geriatric Medicine and Research, 2019)
Skeletal muscle regeneration in mice has traditionally been studied using local freeze burn or snake venom injection models. More recently, a barium chloride (BaCl2)-induced muscle injury model has been established and is gaining popularity due to the relatively simple procedure and accessibility to required reagents. Here we sought to characterize the local and systemic effects of BaCl2-induced muscle injury. For this study, a 1.2% BaCl2 solution was locally administered to the tibialis anterior (TA) muscle and local and systemic phenotypes were analyzed at different timepoints. When 50 μL of the solution was injected unilaterally in the TA muscle, no mortality was observed. However, when 100 μL of the solution was injected, 50% of the mice died within 24 h. Serum analysis of the mice injected with 50 μL of BaCl2 solution at days 1 and 7 revealed changes resembling rhabdomyolysis. At day 1 post-injection of 50 μL of the BaCl2 solution, acute suppurative inflammation was observed in gross examination of the TA muscle, while extensive hemorrhagic necrosis was revealed on histological examination. At day 7, regenerated myofibers with centralized nuclei appeared with the resolution of acute inflammatory infiltration and the muscle tissue displayed molecular signatures consistent with myofiber differentiation. The overall muscle injury and regeneration phenotypes in the BaCl2-induced muscle injury model were similar to those of the well-established freeze burn or snake venom injection models. Taken together, the BaCl2-induced muscle injury model is comparable to conventional muscle injury and regeneration models, with considerations for possible systemic effects.